From causal thinking to wisdom and spirituality: some perspectives on a growing research field in adult (cognitive) development - Kallio, Eeva (Approaching Religion, 2015)
This article concentrates on the latest international trends in the research on psychological development of adults, and especially on the development of cognition. The field of research has been very fragmented, and researchers have kept creating new models one after another to describe their own lines of thought and also seeking for empirical evidence for their models. This has created a rather equivocal picture of the phenomenon itself. The present article attempts to identify the historical roots of the field, and introduces descriptive factors that could conceptually determine the gist of the phenomenon. In this context we will discuss, mainly, research going back to Piaget and Perry, epistemic development, integration of emotion and cognition, plus diverse research in the fields of wisdom and spirituality. The main claim is that these models follow similar a tendency towards holism and progress towards integrative thinking on various domains and fields of human psyche.